Refleksi Pemikiran Politik dan Ekonomi Islam Ibn Khaldun atas Pemerintahan di Indonesia - Regina Citra Arini (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
Today the 45th generation which can be categorized as the first generation that gave birth to the Republic of Indonesia, there are still many people, but in the same period the second and third generations have also emerged. In this case, in the third generation in a country, where this generation is soft and connoisseurs of power and prosperity, without hard work and creativity, the country experiences destruction, because this generation is immersed in luxury, timid and loses the meaning of honor, courage and courage.The BLBI case, Mega KKN at Pertamina, the case of Bank Bali and the architect of social unrest in various regions are indicators of the existence of the second and third generations. Ibn Khaldun believed that a society which at first was good or at least neutral was damaged by a uncivilized group of people.